2022
DOI: 10.1097/md.0000000000030100
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic significance of malnutrition in patients with acute coronary syndrome treated with percutaneous coronary intervention

Abstract: The incidence and impact of malnutrition on acute coronary syndrome (ACS) remain unclear. This study aimed to evaluate the prevalence, clinical relevance, and prognostic outcomes of malnutrition in patients with ACS treated with percutaneous coronary intervention. This retrospective study included 1930 consecutive patients with ACS undergoing percutaneous coronary intervention and assessed their nutritional status using 3 scoring systems: Controlling Nutritional Status score, nutritional risk index (NRI), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The multidimensional assessment can be further deepened through the evaluation of the impact of comorbidities (e.g., Cumulative Illness Rating Scale for Geriatric Patients [ 15 ]), disability and functional status (e.g., activities of daily living and instrumental activities of daily living scores [ 16 ], Barthel Index [ 17 ]), cognitive status (e.g., Mini Mental State Examination [ 18 ], Montreal Cognitive Assessment [ 19 ], Short Portable Mental Status Questionnaire [ 20 ]), as well as sarcopenia and physical performance. The latter are relevant metrics to assess overall health and predict outcomes and, as such, should be part of a multidimensional evaluation [ 21 , 22 ]. Sarcopenia—the loss of skeletal muscle mass, strength and function [ 23 ]—is a powerful predictor of CVD progression, falls, reduced quality of life, and death in patients with CVD [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Assessment Of Frailtymentioning
confidence: 99%
“…The multidimensional assessment can be further deepened through the evaluation of the impact of comorbidities (e.g., Cumulative Illness Rating Scale for Geriatric Patients [ 15 ]), disability and functional status (e.g., activities of daily living and instrumental activities of daily living scores [ 16 ], Barthel Index [ 17 ]), cognitive status (e.g., Mini Mental State Examination [ 18 ], Montreal Cognitive Assessment [ 19 ], Short Portable Mental Status Questionnaire [ 20 ]), as well as sarcopenia and physical performance. The latter are relevant metrics to assess overall health and predict outcomes and, as such, should be part of a multidimensional evaluation [ 21 , 22 ]. Sarcopenia—the loss of skeletal muscle mass, strength and function [ 23 ]—is a powerful predictor of CVD progression, falls, reduced quality of life, and death in patients with CVD [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Assessment Of Frailtymentioning
confidence: 99%
“…PCI is, currently, one of the main invasive treatments for patients with CAD, which can effectively relieve myocardial ischemia and improve myocardial oxygenation, and reduce angina attacks and myocardial infarction [ 7 , 8 ]. Previous studies have shown that the presence of malnutrition may increase the incidence of post-PCI complications and cardiovascular events in elderly SCAD patients, which has a significant impact on the long-term prognosis of patients [ 9 , 10 ]; in addition, malnutrition can induce a chronic inflammatory response in the body, and long-term chronic inflammation can further aggravate malnutrition and oxidative stress, thereby exacerbating endothelial dysfunction and forming a malnutrition-inflammation-atherosclerosis syndrome [ 11 , 12 ]. Therefore, evaluating the nutritional conditions of elderly SCAD patients undergoing PCI during hospitalization may have important prognostic implications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the side effects of malnutrition in cardiovascular diseases have come under the researchers' spotlight. Clinical studies have demonstrated that malnutritional status has negative effects on people affected by cardiovascular diseases including ACS (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%